Uma experiência de trabalho com as famílias em um Centro de Educação Infantil: um olhar dialógico para as práticas educativas - Ferraz, Sandra Marangoni (2011)
The objective of this research was to understand a lasting experience of working with families at the CEI Centro de Educação Infantil (Early Childhood Center), based on protagonists who work there since it was opened: parents, staff members and community representatives. Thus, the questions that have permeated this research were: How was the work with the families perceived by the protagonists? Were there any consequences of that work in the daily routine of CEI employees? This is a qualitative research and, in order to understand the phenomenon, it was based on the ideas of Paulo Freire, in particular what he understands by dialogue. Reflective interviews were used and they were analyzed and discussed with basis on the work of Paulo Freire. The results showed that: some of the parents reflected about their educational practices and seem to have assumed a more dialogic attitude in educating without losing authority; they understood that self-control, persistence, patience, thinking before acting and dialogue are ways to educate their children and overcome how they themselves were educated; although it requires effort, they were able to see that the participation in reflective meetings brought benefits to the education of their children and for their own growth. As for the CEI team and community members, they found that: the work with the families has been extended and is indispensable; the changes related to working with them were gradual and not all participants agreed to the proposal of dialogue; and transformations are possible, but they require work in the medium and long term, because they involve old beliefs and habits; they recognize that they are more united, confident and supportive of the decisions made by the institution. Upon completion of this study, we can see that there is a continuous search for the existence of a dialogic practice by both CEI staff members and community representatives with the families and by some families with their children with the members of the institution. There are concrete signs of change in the practices of the protagonists and they confirm the validity of Freire s concepts with regard to a liberating, democratic and more dignified education